Dinosaurs : a very short introduction - Norman, David, 1952- (New York : Oxford University Press, 2005)
An introduction to dinosaurs that explores how scientists combine anatomy, genetics, forensics, and engineering design to build a picture of what dinosaurs looked like, what they ate, and how they moved and interacted with each other.
Dinosaurs in perspective -- Dinosaur renaissance -- New light on Iguanodon -- Unravelling the genealogy of dinosaurs -- Dinosaurs and warm blood -- What if--birds are dinosaurs? -- Dinosaur research : observation and deduction -- The future of research on the past.
Includes bibliographical references (p. 167-168) and index.
Adult
Keywords: Dinosaurs; Dinosaurs